Connecting World Lexicons: Figurative Language’s Role in BBC News Listening for Intercultural Competence - Stevani, Margaret (LETS: Journal of Linguistics and English Teaching Studies, 2024)
This research investigated the dynamic relationship between figurative language and intercultural competence among university students engaged with BBC News broadcasts. The research focused on language acquisition and listening skills to explore how metaphors, similes, and idiomatic expressions could facilitate communication in diverse linguistic contexts. Guided by a constructivist model and serving in the dual roles of a United Nations ambassador and an English lecturer, the focus was on nurturing critical thinking and autonomous learning within a cohort of 23 English education students in North Sumatra, Indonesia. The primary objective was to emphasize the significance of English proficiency in fostering global partnerships. The findings revealed effective listening skill strategies, including selective attention, recalling prior knowledge, evaluating and repeating the phrases, and contextualization. These strategies yielded benefits such as cultural discovery, enhanced language comprehension, and empathy building. Observations emphasized the importance of background cultural knowledge, managing passage length, and addressing cultural competence topics. Understanding figurative language was essential for cultural students, enhancing creative thinking and fostering comprehensive global citizenship.